Questionable people: inventing modern Jewish selves in the Russian Empire, 1860-1890 - Naṭḳovits, Sveṭlanah (Judaic traditions in literature, music, and art, 2025)
"This title explores how a generation of Jewish artists and intellectuals used self-expression and their artistic work to define themselves and integrate into Russian society in the period of the Great Reforms. From the early 1860s to the 1880s, they fashioned early models of modern Jewish subjectivity in the Russian empire"